Enhanced LPS-induced activation of IL-27 signalling in sarcoidosis. (August 2016) - Ringkowski, Sabine; Loke, Joshua; Huang, Shuying; Ahmadzai, Hasib; Herth, Felix J.F.; Thomas, Paul S.; Herbert, Cristan
Abstract: Rationale: Granulomas in sarcoidosis have recently been described as containing Interleukin (IL)-27, one of the members of the IL-12 family of cytokines, which also includes IL-35. Levels of these cytokines and the IL-27 receptor subunits were hypothesised to differ between patients with sarcoidosis compared to healthy controls in peripheral blood. Methods: Using a cross-sectional study design, plasma and peripheral blood mononuclear cells (PBMC) were collected from patients and control subjects. Protein and mRNA (in PBMC) levels for IL-27 and IL-35 ( IL27, EBI3, IL12A subunits) as well as IL-27 receptor (IL6ST and IL27RA subunits) were assessed spontaneously and following direct (LPS) and indirect (anti-CD3/28 activation beads) macrophage stimulation using RT- PCR, ELISA and flow cytometry. Results: Following stimulation with LPS, PBMC of patients with sarcoidosis displayed significantly enhanced expression of IL27 and EBI3 mRNA ( p  = 0.020 and p  = 0.037 respectively) compared to PBMCs from healthy controls. There was also significantly enhanced production of IL-27 by PBMC from patients with sarcoidosis compared to healthy controls in response to LPS stimulation ( p  = 0.027). IL6ST mRNA and IL6ST protein were significantly lower in patients with sarcoidosis (mRNA p  = 0.0002; MFI p  = 0.0015) whilst IL27RA protein levels were significantly higher in patients with sarcoidosis compared to healthy controls (MFI p  < 0.0001). Plasma IL-35 protein levels did not differ between control and sarcoidosis subjects ( p  = 0.23). Conclusion: These results suggest there may be exaggerated activation of IL-27 signalling in response to LPS in sarcoidosis. Highlights: LPS induces significantly more IL-27 in PBMCs of patients with sarcoidosis. IL27RA MFI is significantly elevated on Th cells of patients with sarcoidosis. IL6ST is significantly lower in PBMC and on Th cells of patients with sarcoidosis. IL-27 receptor expression correlates with DLCO in patients with sarcoidosis. IL-35 is not significantly altered in peripheral blood of patients with sarcoidosis.